Effect of Metatarsal Pad Use on Spatiotemporal Gait Parameters on Forefoot Pain - Sevina, Adisti Noer; Triyani; Anatasia, Suci; Hanawati, Rizan Yuni (Journal of Prosthetics Orthotics and Science Technology, 2023)
Background: Wearing high heels (>2–2.5 cm) increases forefoot pain risk. Metatarsal pads are often used for pain relief, but their impact on gait parameters remains unclear. Purpose: To analyse the effect of metatarsal pads on spatiotemporal gait parameters in individuals with forefoot pain from high heels. Method: A one-sample pre-test post-test study was conducted with 30 participants (aged 18–20). Pain levels and gait parameters (velocity, step length, stride length, stance phase duration) were measured before and after 2 weeks of pad use. Result: Pain changes were inconsistent: 10 participants reported less pain, 9 had more pain, and 11 felt no difference, with no significant correlation (p>0.05). Gait parameters showed minor changes: increased velocity (+0.718 km/h), shorter step length (?14 mm), shorter stride length (?3 mm), and faster stance phase (?0.314 s). However, these changes were statistically insignificant (velocity: p=0.477; step length: p=0.758; stride length: p=0.489; stance phase: p=0.295). Conclusion: Metatarsal pads may reduce forefoot pain in some individuals but lack a consistent significant effect. While slight gait adjustments occurred, only velocity and stance phase duration showed potential influence, whereas step and stride length remained unaffected. Further research is needed to confirm clinical relevance.